Governing prostitution in colonial Delhi: from cantonment regulations to international hygiene (1864-1939) - Legg, Stephen (Taylor & Francis, 2009)
This article explores the social and governmental geographies of colonial Delhi, India. It seeks contrasts and comparisons between two periods in the city's history. The first period is delimited by the ‘Mutiny’ of 1857 and the transfer of the capital of British India to the city in 1911. The second period ends in 1947 with Indian independence and marks Delhi's time as part of the capital region. The focus of study across these periods is the way in which governmental rationalities were devised to deal with the biopolitical problem of the prostitute. The first period saw a focus on disciplining prostitutes and registering brothels so as to protect the military from venereal disease. The second period saw an increasing focus on the health risks that prostitutes posed to the broader population, and the emergence of extra-governmental agencies that sought to implement programmes of social and moral hygiene in Delhi. Across both periods, Delhi was shaped by national and international forces, both within and without government, yet the social geographies of the city bequeathed legacies of the nineteenth century to the interwar era that international hygienists had to negotiate.